2012
DOI: 10.1002/hed.21874
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of limited‐volume perioperative high‐dose‐rate brachytherapy and wide‐field external irradiation in resected head and neck cancer

Abstract: Complications and locoregional failure rates were similar to those reported in the reference standards despite a much smaller treatment volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Periopertive high dose rate brachytherapy alone after R0 resection has been associated with 9 year cancer-specific survival rate of 47.9%. 4 Martinez et al reported the 4 year local control rate and overall survival were 85.6 and 46.4%, respectively in head and neck cancers treated with reirradiation using PHDRB. 13,14 Treatment-related acute side-effects include bleeding, fistula, graft failure, delayed wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periopertive high dose rate brachytherapy alone after R0 resection has been associated with 9 year cancer-specific survival rate of 47.9%. 4 Martinez et al reported the 4 year local control rate and overall survival were 85.6 and 46.4%, respectively in head and neck cancers treated with reirradiation using PHDRB. 13,14 Treatment-related acute side-effects include bleeding, fistula, graft failure, delayed wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Gaztanaga et al have shown perioperative high dose rate brachytherapy to have equivalent treatment outcomes when compared to wide field radiotherapy with 5 year locoregional control rates from 60.9 to 79.4%. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically utilized most frequently in the treatment of gynecologic malignancies [21][22][23], BRT is now also an established therapeutic modality in the management of residual, recurrent and metastatic tumors of the head and neck region [15,16,[24][25][26][27][28][29]. EBRT of the sinonasal tract and nasopharynx may result in both acute and late toxicities due to secondary radiation exposure to the optic chiasm, optic nerve, orbit and brainstem, especially in the setting of prior skull base irradiation.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…(2 fracciones al día -b.i.d.) en el caso de la braquiterapia HDR [138][139][140][141][142] , y de 60 Gy en el caso de la braquiterapia LDR administrados durante 4-5 días. 143,144 Las series de braquiterapia postoperatoria informan de tasas de control locorregional a 5 años entre el 74% y el 93%, 118,135,145 con los mejores resultados en aquellos tumores con estadio precoz tratados con braquiterapia postoperatoria exclusiva y los peores resultados en estadios avanzados tratados con la combinación de radioterapia externa y braquiterapia postoperatoria.…”
Section: Indicaciones De La Braquiterapiaunclassified